Endothelial c-Myc knockout disrupts metabolic homeostasis and triggers the development of obesity - Machi, Jacqueline F.; Altilio, Isabella; Qi, Yue; Morales, Alejo A.; Silvestre, Diego H.; Hernandez, Diana R.; Da Costa-Santos, Nicolas; Santana, Aline G.; Neghabi, Mehrnoosh; Nategh, Parisa; Castro, Thiago L.; Werneck-de-Castro, João P.; et al. (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Obesity is a major risk factor associated with multiple pathological conditions including diabetes and cardiovascular disease. Endothelial dysfunction is an early predictor of obesity. However, little is known regarding how early endothelial changes trigger obesity. In the present work we report a novel endothelial-mediated mechanism essential for regulation of metabolic homeostasis, driven by c-Myc. Methods: We used conditional knockout (EC-Myc KO) and overexpression (EC-Myc OE) mouse models to investigate the role of endothelial-specific c-Myc in metabolic homeostasis during aging and high-fat diet exposure. Body weight and metabolic parameters were collected over time and tissue samples collected at endpoint for biochemical, pathology and RNA-sequencing analysis. Animals exposed to high-fat diet were evaluated for cardiac dysfunction. Results: In the present study we demonstrate that EC-Myc KO triggers endothelial dysfunction, which precedes progressive increase in body weight during aging, under normal dietary conditions. At endpoint, EC-Myc KO animals showed significant increase in white adipose tissue mass relative to control littermates, which was associated with sex-specific changes in whole body metabolism and increase in systemic leptin. Overexpression of endothelial c-Myc attenuated diet-induced obesity and visceral fat accumulation and prevented the development of glucose tolerance and cardiac dysfunction. Transcriptome analysis of skeletal muscle suggests that the protective effects promoted by endothelial c-Myc overexpression are associated with the expression of genes known to increase weight loss, energy expenditure and glucose tolerance. Discussion: Our results show a novel important role for endothelial c-Myc in regulating metabolic homeostasis and suggests its potential targeting in preventing obesity and associated complications such as diabetes type-2 and cardiovascular dysfunction.